Clinical impact and predictors of complete ST segment resolution after primary percutaneous coronary intervention: A subanalysis of the ATLANTIC Trial. Issue 3 (April 2019) - Fabris, Enrico; van 't Hof, Arnoud; Hamm, Christian W; Lapostolle, Frédéric; Lassen, Jens F; Goodman, Shaun G; ten Berg, Jurriën M; Bolognese, Leonardo; Cequier, Angel; Chettibi, Mohamed; Hammett, Christopher J; Huber, Kurt; et al.
Background: In the ATLANTIC (Administration of Ticagrelor in the catheterization laboratory or in the Ambulance for New ST elevation myocardial Infarction to open the Coronary artery) trial the early use of aspirin, anticoagulation, and ticagrelor coupled with very short medical contact-to-balloon times represent good indicators of optimal treatment of ST-elevation myocardial infarction and an ideal setting to explore which factors may influence coronary reperfusion beyond a well-established pre-hospital system. Methods: This study sought to evaluate predictors of complete ST-segment resolution after percutaneous coronary intervention in ST-elevation myocardial infarction patients enrolled in the ATLANTIC trial. ST-segment analysis was performed on electrocardiograms recorded at the time of inclusion (pre-hospital electrocardiogram), and one hour after percutaneous coronary intervention (post-percutaneous coronary intervention electrocardiogram) by an independent core laboratory. Complete ST-segment resolution was defined as ≥70% ST-segment resolution. Results: Complete ST-segment resolution occurred post-percutaneous coronary intervention in 54.9% ( n =800/1456) of patients and predicted lower 30-day composite major adverse cardiovascular and cerebrovascular events (odds ratio 0.35, 95% confidence interval 0.19–0.65; p < 0.01), definite stent thrombosis (odds ratio 0.18, 95% confidence interval 0.02–0.88; p =0.03), and total mortality (odds ratio 0.43, 95% confidence interval 0.19–0.97; p =0.04). In multivariate analysis, independent negative predictors of complete ST-segment resolution were the time from symptoms to pre-hospital electrocardiogram (odds ratio 0.91, 95% confidence interval 0.85–0.98; p < 0.01) and diabetes mellitus (odds ratio 0.6, 95% confidence interval 0.44–0.83; p < 0.01); pre-hospital ticagrelor treatment showed a favorable trend for complete ST-segment resolution (odds ratio 1.22, 95% confidence interval 0.99–1.51; p =0.06). Conclusions: This study confirmed that post-percutaneous coronary intervention complete ST-segment resolution is a valid surrogate marker for cardiovascular clinical outcomes. In the current era of ST-elevation myocardial infarction reperfusion, patients' delay and diabetes mellitus are independent predictors of poor reperfusion and need specific attention in the future.